Quantitative Geochemistry - Zou, Haibo (World Scientific, 2017)
Modern geochemistry possesses not only the vigor of geology and chemistry, but also the rigor of mathematics. This book presents quantitative treatments of a wide range of fundamental problems related to geochemistry and geology. It shows that trace elements, isotopes, and equations are integrative tools in modern geochemistry for studying various Earth processes. In many chapters, simple models are presented first, and more parameters are gradually added so that the sophisticated models can be perceived as natural outgrowths of simple ones. The book will help scientists and graduate students in Earth Sciences improve their capacity to understand, apply, criticize, and appreciate the available models and possibly to develop their own models. This understanding will provide penetrating insights into fundamental principles in geochemistry, geology, analytical chemistry, and mass spectrometry, as well as any other fields in the natural sciences.